The effect of succession stage on seed rain and seedling recruitment in overgrown Molinia caeruleae meadows - Kostrakiewicz-Gierałt, Kinga (Archives of Biological Sciences, 2017)
Investigations into the effect of succession stage on seed rain and seedling recruitment were conducted in Kraków-Kostrze (southern Poland) in 2014 and 2015. Observations were carried out in Molinia caeruleae meadows representing early (Patch I), temporary (Patch II) and advanced (Patch III) stage of secondary succession. Patch I was dominated by meadow species creating delicate stems, Patch II abounded in large tussock grasses and tall-growing rhizomatous grasses and Patch III was overgrown by willow shrubs and bordered by trees. The number of seeds and taxa in the seed rain decreased gradually in the successive study sites. Species resident in the standing vegetation were the most abundantly represented in the seed rain and their share augmented remarkably in Patch III, most likely due to its spatial isolation by the surrounding shrubs and trees. The share of seedlings and taxa in artificially made gaps in the plant cover and litter decreases along the successional gradient. The majority of taxa appearing in the seedling pool of all the patches occurred in the seed rain, while the taxa in the soil seed-bank reserves were modestly represented only in Patches I and II. Combining the obtained results and published data, it can be stated that, being abundant in the seed rain, the best colonizers show the greatest germination capability. Although the best colonizers are meadow taxa, fast-growing weeds, trees as well as alien, invasive species also appeared in the seedling pool. https://doi.org/10.2298/ABS160722127K Received: July 22, 2016; Revised: September 23, 2016; Accepted: October 12, 2016; Published online: November 9, 2016 How to cite: Kostrakiewicz-Gierałt K. The effect of succession stage on seed rain and seedling recruitment in overgrown Molinia caeruleae meadows. Arch Biol Sci. 2017;69(3):513-22.